ANALYSIS OF MILLENIALS’ PRODUCTIVITY IN THE MANUFACTURING INDUSTRY - Grace Amin; Bayu Setiawan (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2022)
This study aims to determine the influence of the working environment, stress, opportunities for innovation, and motivation toward employee productivity of the millennial generation in the workplace. A quantitative approach and multiple linear regression were used to analyze data from 107 respondents. The result of this research shows that the working environment, stress, and opportunities for innovation have a significant influence on millennials’ productivity while motivation has no significant influence. All of the independent variables simultaneously influence the millennials’ productivity with the coefficient of determination (adjusted R2) around 80.1%. Manufacturing companies need to provide a comfortable environment that encourages millennial employees to show innovation and increase productivity.